Coastal groundwater response to climate variability coupling in California and Portugal - Malmgren, Katherine Allise (2021)
Aquifers are a fundamental source of freshwater, yet they are particularly vulnerable in coastal Mediterranean regions due to climate and anthropogenic pressures. This comparative study examines the interrelationships between ocean-atmosphere teleconnections, groundwater levels and precipitation in coastal aquifers of California and Portugal, deepening the understanding of climate variability coupling behaviors across mirrored Mediterranean climates. Piezometric and precipitation records (1982-2019) are analyzed using singular spectral analysis, wavelet transform and lag correlation methods. Additionally, the development of a groundwater sustainability index (GSI) exposes vulnerability to drought and provides useful insights for future groundwater management and security. Singular spectral analysis identify signals consistent with the six dominant climate patterns, the Pacific Decadal Oscillation (PDO), the El Niño-Southern Oscillation (ENSO), and the Pacific/North American Oscillation (PNA) in California, and the North Atlantic Oscillation (NAO), the Eastern Atlantic Oscillation (EA) and the Scandinavian Pattern (SCAND) in Portugal. Lower frequency oscillations have a greater influence on hydrologic patterns, with PDO (52.75%) and NAO (46.25%) accounting for the largest amount of groundwater level variability. Wavelet coherences show non-stationary covariability between climate patterns and groundwater levels in distinct period bands; 4-8 years for PDO, 2-4 years for ENSO, 1-2 years for PNA, 5-8 years for NAO, 2-4 years for EA and 2-8 years for SCAND, presenting some dispersion of the low frequency signals. Wavelet coherence patterns also show that coupled climate patterns (NAO+ EA- and paired PDO and ENSO phases) are associated with major drought periods in both regions. Finally, the GSI classify highly vulnerable and low sustainability aquifers in southern California and in northern Portugal, warranting further policy and mitigation measures in these at-risk areas. The current work shows how pairing hydro-climatological knowledge with a GSI can provide insightful knowledge, which can be used to enrich and inform effective sustainable groundwater management policies.